Editorial: Analytic Science-Engaged Theology - Leidenhag, Joanna; Göcke, Benedikt Paul (TheoLogica: An International Journal for Philosophy of Religion and Philosophical Theology, 2023)
Analytic theology and Science-Engaged Theology are two of the most exciting movements within theology in recent years, and have much in common. Both are interdisciplinary endeavours that engage other sub-disciplines (analytic philosophy and the natural and behavioural sciences, respectively) in the service of theology. Many (although not all) of the same scholars actively contribute to both movements. Furthermore, analytic theology and science-engaged theology both maintain the primacy and integrity of the theological task, whilst simultaneously inviting other disciplines to enrich theological reflection, criticism, and confession.